The Study of the Effects of Knowledge Management (KM) on Customer Relationship Management (CRM) in Refah Bank (case study: Kurdistan Province) - Adel Salavati; Parviz Kafcheh; Kayvan Salehpoor (مدیریت بهره وری, 2011)
This article studies the effects of knowledge management on customer relationship management. Our research method is descriptive and survey in nature. The statistical population is composed of all the employees serving in all the branches of Refah Bank across Kurdistan totaling 180 people. In this study, we applied Principal Components Analysis (PCA) and structural relations (LISREL) to explore the factors and expand the items of our questionnaire. Our data were analyzed through path analysis and the Model of Structural Equations. The findings of our research indicate that knowledge management has got some positive and meaningful effects on different aspects of managing relations with customers (i.e., customer satisfaction, customer loyalty, customer absorption, and interaction) through knowledge resources. According to our findings, the highest rate of effectiveness of knowledge management has been on customer satisfaction followed by other variables including customer loyalty, absorption, and interaction with customer, respectively.